MEMETIC INTENTION AND THE IMPLICATIONS FOR AGENCY - Davidson, Emily (The Oracle, 2021)
The mind-body dilemma has historically been one of the more pernicious problems plaguing philosophers’ intent on solidifying the mind as a construct for empirical inquiry. Thomas Nagel so aptly stated, “Consciousness is what makes the mind-body problem really intractable.”1 The areas of focus in mind research that deal with the essential foundations of consciousness, like our sense of agency, often find themselves mired in conceptual elements; they are unable to produce lasting, universal, operational definitions because the mind-body problem frames the issue as unwaveringly abstract from its inception. While certainly ambitious, my hope is that my endeavours here may be useful in framing a dialogue about elements of consciousness in a familiar, scientific framework that help to, at minimum, narrow the impact of the mind-body problem on the study of consciousness. In order to accomplish this, I will first attempt to tether pre-existing filaments to create a workable analogy between evolutionary biology and the study of the mind. With such a paradigm established, I will then elaborate on the idea of the meme as being analogous to the gene by introducing the concept of memetic alleles. I will then attempt to demonstrate how this type of bottom-up approach can be useful by demonstrating its applicability to the thorny philosophical realm of intention. Finally, I will attempt to show how this can formulate the necessary infrastructure to bring seemingly unfalsifiable arguments like the hard problem of consciousness within the realm of scientific exploration. This inquiry will by no means be exhaustive, but will act as an initial step in the direction of creating falsifiable parameters in areas previously thought to hold little room for systematization.